Fetal Wilm's tumor detection preceding the development of isolated lateralized overgrowth of the limb: a case report and review of literature - Bechara, Elie; Saadé, Chloé; Geagea, Caroline; Charouf, Daniel; Abou Jaoude, Pauline (Frontiers in Pediatrics, 2024)
Fetal Wilms tumor (WT) is extremely rare, but with advances in fetal imaging, more cases are being reported. The management of these cases remains challenging. Herein, we present the case of a full-term female infant diagnosed antenatally at 32 weeks of gestation with a right solid renal mass detected on routine prenatal ultrasound without polyhydramnios. At birth, the infant was healthy, with no evidence of dysmorphic features or abnormal laboratory tests to suggest a predisposition syndrome. Her family history was also unremarkable. A successful radical right nephrectomy was performed on day 2 of life revealing a classic WT. She received vincristine as adjuvant chemotherapy without any complications. At the age of 1 month, the infant developed isolated lateralized overgrowth of the right lower limb suspicious of Beckwith–Wiedemann syndrome. At the latest follow-up of 4 years, the child is healthy and disease-free with conserved asymmetry of lower limbs. The case provides insights into the challenging diagnosis and treatment of fetal WT. A review of the literature suggests that the presence of polyhydramnios is a worse prognostic factor while the combination of best supportive care and surgery remains the best management. Fetal WT can be associated with predisposition syndromes; however, their first manifestations can develop after the diagnosis of cancer has been made, as in our patient. We propose starting active surveillance programs and genetic testing for any case of fetal WT.